Pengaruh Kepuasan Pelanggan dan Pelayanan Terhadap Peningkatan Penjualan di PT. Jaya Anugerah Sukses Abadi (Brastagi Supermarket) - Ennisah Ennisah; Nur Augus Fahmi; Tika Indria (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The research analysis aims to determine whether customer satisfaction has a partial positive and significant effect on increasing sales at PT. Jaya Anugerah Sukses Abadi (Brastagi Supermarket). Does service have a partial positive and significant effect on increasing sales at PT. Jaya Anugerah Sukses Abadi (Brastagi Supermarket). Do customer satisfaction and service simultaneously have a positive and significant effect on increasing sales at PT. Jaya Anugerah Sukses Abadi (Brastagi Supermarket). This study uses multiple linear regression. The sample research was conducted using the